The Effect of Liquidity Ratio on Profitability Ratio of Pt Anugerah Kagun Karya Utama Tbk Period 2011-2022 - Saifudin Saifudin (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This study aims to determine the effect of the liquidity ratio on the profitability ratio at PT Anugerah Kagun Karya Utama Tbk. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Current Ratio obtained an average value of 19.34%. The variable Return On Assets obtained an average value of 1.47%. The Current Ratio has a positive and significant effect on Return On Assets with a regression equation value Y = -1.075 + 0.132X, and a correlation coefficient value of 0.676 or having a strong relationship with a determination value of 45.7%. The hypothesis test obtained a significance of 0.016 <0.05.